Dymorfizm płciowy w pre- i postnatalnym rozwoju krtani człowieka - Bożiłow, Władimir; Betlejewski, Stanisław; Sawicki, Konstanty; Winiarski, Piotr; Krakowiak, Janusz (Anthropological Review, 1993)
Fourteen diameters, generally characterizing the larynxes of Poles from the 4th fetal month to the 90th year of life were analysed. The authors' material consisted of 200 normal fetuses. Postnatal material (956 specimes) was reinterpreted after recounting data from literature